LEGAL ANALYSIS OF NO QUID PRO QUO PRINCIPLE IN SPONSORSHIP FOR INDONESIAN HEALTHCARE PROFESSIONALS - Himawati, Hetsa; Triyana, Heribertus Jaka (TANJUNGPURA LAW JOURNAL, 2026)
Abstract   The Minister of Health Regulation (Permenkes) No. 58/2016 regulates the provision of sponsorship from industry to healthcare professionals to enhance competencies and the quality of health services. In practice, however, sponsorship may compromise the independence of clinical decision-making, particularly in prescribing products manufactured or marketed by the sponsoring company. This article assesses the extent to which Permenkes 58/2016 reflects the principles of justice and utility and examines the adoption of the no quid pro quo doctrine as an ethical constraint for safeguarding professional independence and preventing conflicts of interest in the governance of sponsorship. It complements prior research which predominantly examined sponsorship from the perspectives of gratuities and professional ethics. This study employs a normative juridical method through a review of legislation, legal principles, doctrine, and professional ethics frameworks, accompanied by a systematic analysis of the relationships among healthcare professionals, institutions, and industry. The findings indicate that Permenkes 58/2016 incorporates the principle of justice from the perspective of fair equality of opportunity. Nevertheless, distributive and corrective justice remain incomplete due to the absence of objective selection mechanisms, equitable allocation procedures, and clear limits on sponsorship, as well as the lack of sanctions for healthcare institutions and industry actors. Utility is acknowledged in a utilitarian orientation, but benefits remain concentrated at the individual level and are not sufficiently directed toward broader health-system strengthening. Although no quid pro quo is recognized normatively, it is not supported by a comprehensive conflict-of-interest governance framework, as reflected in PP 28/2024, Permenkes 24/2019, the Government Administration Law, and anti-corruption law. Accordingly, Permenkes 58/2016 should be reformed by ensuring transparent access to sponsorship based on objective selection criteria, defining clear limits and eligibility criteria for sponsorship funding, extending sanctions to all stakeholders, strengthening mechanisms for conflict-of-interest declaration and mitigation, and reorienting sponsorship to support a sustainable healthcare system. Abstrak   Permenkes 58/2016 mengatur pemberian sponsorship dari industri kepada tenaga kesehatan untuk meningkatkan kompetensi dan kualitas layanan kesehatan. Namun, dalam praktiknya, sponsorship masih berpotensi memengaruhi independensi pengambilan keputusan medis, terutama dalam peresepan produk-produk yang diproduksi atau dipasarkan oleh industri pemberi sponsorship. Artikel ini bertujuan menilai penerapan asas keadilan dan kemanfaatan dalam Permenkes 58/2016 serta mengkaji adopsi doktrin no quid pro quo sebagai pagar etik guna menjaga independensi tenaga kesehatan agar sponsorship dikelola secara adil, bermanfaat, dan bebas dari konflik kepentingan. Penelitian ini berkontribusi dengan menganalisis sponsorship dalam kerangka asas hukum keadilan dan kemanfaatan serta doktrin no quid pro quo, sehingga melengkapi penelitian terdahulu yang umumnya menelaah sponsorship terutama dari perspektif gratifikasi dan etika profesi. Penelitian ini menggunakan metode yuridis normatif melalui telaah peraturan perundang-undangan, asas-asas hukum, doktrin, kerangka etik profesi, disertai analisis sistematis atas relasi antara tenaga kesehatan, institusi, dan industri. Hasil penelitian menunjukkan bahwa Permenkes 58/2016 telah memuat asas keadilan melalui perspektif fair equality of opportunity. Namun, keadilan distributif dan keadilan korektif belum sepenuhnya terpenuhi karena ketiadaan mekanisme seleksi objektif, prosedur pemerataan, dan batas kewajaran sponsorship, serta belum adanya pengaturan sanksi bagi institusi kesehatan dan industri sebagai aktor dalam skema sponsorship. Asas kemanfaatan telah tercermin dalam pandangan utilitarianisme, tetapi manfaat sponsorship masih dominan pada tingkat individu tenaga kesehatan dan belum diarahkan pada penguatan sistem pelayanan kesehatan secara lebih luas. Prinsip no quid pro quo telah diadopsi secara normatif, namun belum ditopang oleh kerangka tata kelola konflik kepentingan yang komprehensif sebagaimana diatur dalam PP 28/2024, Permenkes 24/2019, UU Administrasi Pemerintahan, dan UU Tipikor. Penyempurnaan Permenkes 58/2016 diperlukan melalui pembukaan akses sponsorship secara transparan dengan kriteria seleksi objektif, penetapan standar kewajaran besaran sponsorship, perluasan sanksi bagi seluruh pemangku kepentingan, penguatan mekanisme deklarasi serta mitigasi konflik kepentingan, serta reorientasi sponsorship agar turut mendukung penguatan sistem pelayanan kesehatan secara berkelanjutan.